The Efficacy of the Novel TSPO Ligands 2-Cl-MGV-1 and 2,4-Di-Cl-MGV-1 Compared to the Classical TSPO Ligand PK 11195 to Counteract the Release of Chemokines from LPS-Stimulated BV-2 Microglial Cells - Monga, Sheelu (Biology (Basel), 2020)
The impact of ligands of the 18 kDa translocator protein (TSPO) on the release of chemokines is not vastly investigated. In the present study, we assessed the effect of our novel TSPO ligands 2-Cl-MGV-1 and 2,4-Di-Cl-MGV-1 compared to the classical TSPO ligand PK 11195 on chemokine release in LPS-stimulated BV-2 microglial cells. As per the effect of 2-Cl-MGV-1, CCL2, CCL3, and CCL5 were inhibited by 90%, CCL8 by 97%, and IL-2 by 77% (p < 0.05 for all). 2,4-Di-Cl-MGV-1 inhibited CCL2 release by 92%, CCL3 by 91%, CCL5 by 90%, CCL8 by 89%, and IL-2 by 80% (p < 0.05 for all). PK 11195 exhibited weaker inhibitory effects: CCL2 by 22%, CCL3 by 83%, CCL5 by 34%, CCL8 by 41%, and the cytokine IL-2 by 14% (p < 0.05 for all). Thus, it appears that the novel TSPO ligands are potent suppressors of LPS-stimulated BV-2 microglial cells, and their inhibitory effect is larger than that of PK 11195. Such immunomodulatory effects on microglial cells may be relevant to the treatment of neurodegenerative and neuroinflammatory diseases.